Activation mechanism of lead ions in the flotation of sulfidized azurite with xanthate as collector. (15th March 2021) - Zhang, Qian; Wen, Shuming; Feng, Qicheng; Liu, Yuebing
Highlights: Flotation recovery of azurite was improved after sulfidization followed by addition of lead ions. Lead ions could adsorb onto sulfidized azurite surfaces and generated Pb–S species. Addition of lead ions increased the adsorption of xanthate species onto sulfidized azurite surfaces. Abstract: Metal ions are commonly used to activate oxide minerals and improve the collector adsorption on the mineral surface. In this work, lead ions were added after azurite was sulfidized with Na2 S, and the effect of lead ions on the flotation of sulfidized azurite was investigated. Micro-flotation tests were performed to study the flotation behavior after sulfidized azurite was treated with lead ions, and the activation mechanism was revealed by zeta potential determination, X-ray photoelectron spectroscopy (XPS) analysis, time-of-flight secondary ion mass spectrometry (ToF-SIMS), Fourier-transform infrared (FT-IR) spectroscopy, and ultraviolet spectroscopy measurements. The flotation results showed that the azurite recovery increased when a low concentration of lead ions was poured into the pulp solution in the presence of Na2 S. Zeta potential determination indicated that chemisorption occurred when the sulfidized azurite surface was modified with lead ions. The XPS results showed that Pb–S species formed on the sulfidized azurite surface treated with lead ions. ToF-SIMS analysis showed that S −, S2 −, SO3 −, and Pb 2+ ions were present on the azurite surface and the thickness of the S species in the azurite–Na2 S–Pb(II) system was larger than in the azurite–Na2 S system. FT-IR showed that the interaction between the lead ions and sulfidized azurite surfaces improved the xanthate attachment to the mineral surface. These results illustrated that addition of lead ions after sulfidization of azurite with Na2 S was beneficial to the flotation recovery of copper oxide ores containing azurite.